Uso de câmara úmida em enxertia convencional de maracujazeiro-amarelo sobre três porta-enxertos - Corrêa, Luiz de Souza [UNESP]; Cavichioli, José Carlos; de Oliveira, João Carlos [UNESP]; Boliani, Aparecida Conceição [UNESP] (My University, 2010)
The grafting of passion fruit might be the solution for root disease control. Thus, with the objective of evaluating the development and survival of yellow passion fruit plants grafted on three rootstocks during the nursery phase, an experiment was carried out in Adamantina, SP, Brazil, from December 2005 to April 2006. The experimental design was in randomized blocks in factorial scheme 3 × 2, with four replications. The studied factors were three rootstocks (P. edulis, P. alata and P.gibertii) in two environments (with and without humid chamber). The conventional grafting by cleft grafting method was used. The variables evaluated were: graft survival percentage and height, rootstock and graft stem diameter, leaf number, aerial portion and root fresh and dry weight. The species P. edulis and P. gibertii showed the best performance among the rootstocks. The greater survival percentages were observed in P. edulis and P. gibertii, with 100% and 98,8%. The use of P. alata as rootstocks to yellow passion fruit is viable, in despite of inferior results in the majority of the analyzed variable. The use of humid chamber favored the survival of grafts in P. alata.
Use of humid chamber in conventional grafting of yellow passion fruit on three rootstocks
Keywords: Asexual propagation; Passiflora sp.; Protected environment; Scion production